A technique for estimating 4D‐CBCT using prior knowledge and limited‐angle projections. Issue 12 (5th November 2013) - Zhang, You; Yin, Fang‐Fang; Segars, W. Paul; Ren, Lei
Abstract : Purpose: : To develop a technique to estimate onboard 4D‐CBCT using prior information and limited‐angle projections for potential 4D target verification of lung radiotherapy. Methods: : Each phase of onboard 4D‐CBCT is considered as a deformation from one selected phase (prior volume) of the planning 4D‐CT. The deformation field maps (DFMs) are solved using a motion modeling and free‐form deformation (MM‐FD) technique. In the MM‐FD technique, the DFMs are estimated using a motion model which is extracted from planning 4D‐CT based on principal component analysis (PCA). The motion model parameters are optimized by matching the digitally reconstructed radiographs of the deformed volumes to the limited‐angle onboard projections (data fidelity constraint). Afterward, the estimated DFMs are fine‐tuned using a FD model based on data fidelity constraint and deformation energy minimization. The 4D digital extended‐cardiac‐torso phantom was used to evaluate the MM‐FD technique. A lung patient with a 30 mm diameter lesion was simulated with various anatomical and respirational changes from planning 4D‐CT to onboard volume, including changes of respiration amplitude, lesion size and lesion average‐position, and phase shift between lesion and body respiratory cycle. The lesions were contoured in both the estimated and "ground‐truth" onboard 4D‐CBCT for comparison. 3D volume percentage‐difference (VPD) and center‐of‐mass shift (COMS) were calculated to evaluate the estimation accuracy of three techniques: MM‐FD, MM‐only, and FD‐only. Different onboard projection acquisition scenarios and projection noise levels were simulated to investigate their effects on the estimation accuracy. Results: : For all simulated patient and projection acquisition scenarios, the mean VPD (±S.D.)/COMS (±S.D.) between lesions in prior images and "ground‐truth" onboard images were 136.11% (±42.76%)/15.5 mm (±3.9 mm). Using orthogonal‐view 15°‐each scan angle, the mean VPD/COMS between the lesion in estimated and "ground‐truth" onboard images for MM‐only, FD‐only, and MM‐FD techniques were 60.10% (±27.17%)/4.9 mm (±3.0 mm), 96.07% (±31.48%)/12.1 mm (±3.9 mm) and 11.45% (±9.37%)/1.3 mm (±1.3 mm), respectively. For orthogonal‐view 30°‐each scan angle, the corresponding results were 59.16% (±26.66%)/4.9 mm (±3.0 mm), 75.98% (±27.21%)/9.9 mm (±4.0 mm), and 5.22% (±2.12%)/0.5 mm (±0.4 mm). For single‐view scan angles of 3°, 30°, and 60°, the results for MM‐FD technique were 32.77% (±17.87%)/3.2 mm (±2.2 mm), 24.57% (±18.18%)/2.9 mm (±2.0 mm), and 10.48% (±9.50%)/1.1 mm (±1.3 mm), respectively. For projection angular‐sampling‐intervals of 0.6°, 1.2°, and 2.5° with the orthogonal‐view 30°‐each scan angle, the MM‐FD technique generated similar VPD (maximum deviation 2.91%) and COMS (maximum deviation 0.6 mm), while sparser sampling yielded larger VPD/COMS. With equal number of projections, the estimation results using scattered 360° scan angle were slightly better than those using orthogonal‐view 30°‐each scan angle. The estimation accuracy of MM‐FD technique declined as noise level increased. Conclusions: : The MM‐FD technique substantially improves the estimation accuracy for onboard 4D‐CBCT using prior planning 4D‐CT and limited‐angle projections, compared to the MM‐only and FD‐only techniques. It can potentially be used for the inter/intrafractional 4D‐localization verification.